Prognosis of Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from the Institute of Neurology, Queen Square, London, UK, report results of longitudinal cohort studies of prognosis in epilepsy in adults and children and focus particularly on the National General Practice Study of Epilepsy (NGPSE) in 1195 patients initiated in 1983.